Effect of the Glycerol Addition on the Physical Characteristics of Biodegradable Plastic Made from Oil Palm Empty Fruit Bunch - Hamzah, Farida Hanum; Sitompul, Fitra Fatthoni; Ayu, Dewi Fortuna; Pramana, Angga (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractPlastic is a packaging material used as a container to protect and store food as well as non-food products essential for the community, specifically in Indonesia. This study aims to examine the effect of glycerol addition as a plasticizer on the physical characteristics of biodegradable plastic made from oil palm empty fruit bunches (OPEFBs). It was conducted through an experiment using a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The treatments include P1, P2, P3, P4, and P5 with 1%, 1.5%, 2%, 2.5%, and 3% glycerol, respectively, in the formulation of biodegradable plastic. The results showed that the addition of glycerol had significant effects on water resistance, vapor transmission rate, tensile strength, and elongation, but had no significant effect on the biodegradability of plastic. Furthermore, the addition of glycerol as a plasticizer improved the elongation of biodegradable plastic made from OPEFB, but did not improve the characteristics of water resistance, vapor transmission rate, and tensile strength. The P1 treatment produced the best result as it generated a water resistance of 2.226%, vapor transmission rate of 16.306 g/m2/hour, tensile strength of 2.430 MPa, and elongation of 18.950%. In addition, the biodegradable plastic was able to decompose in two weeks.Keywords: biodegradable plastic, glycerol, oil palm empty fruit bunch AbstrakPlastik merupakan bahan kemasan yang digunakan sebagai wadah untuk melindungi dan menyimpan produk pangan dan non-pangan yang penting bagi masyarakat, khususnya di Indonesia. Tujuan penelitian ini adalah untuk menguji pengaruh penambahan gliserol sebagai plasticizer terhadap karakteristik fisik plastik biodegradable berbahan tandan kosong kelapa sawit. Penelitian ini dilakukan melalui eksperimen dengan menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari 5 perlakuan dan 3 ulangan. Perlakuan dalam penelitian ini adalah P1, P2, P3, dan P4 dengan penambahan gliserol berturut-turut sebanyak 1%, 1,5%, 2%, 2,5%, dan 3% dalam formulasi plastik biodegradable. Hasil penelitian ini menunjukkan bahwa penambahan gliserol berpengaruh nyata terhadap ketahanan air, laju transmisi uap air, kekuatan tarik, dan perpanjangan, namun tidak berpengaruh nyata terhadap uji biodegradabilitas plastik biodegradable. Penambahan gliserol sebagai plasticizer meningkatkan elongasi plastik biodegradable dari tandan kosong kelapa sawit, namun tidak dapat meningkatkan karakteristik ketahanan air, laju transmisi uap air, dan kekuatan tarik. Perlakuan P1 adalah yang terbaik karena menghasilkan daya tahan air sebesar 2,226%, laju transmisi uap air sebesar 16,306 g/m2/jam, kuat tarik sebesar 2,430 MPa, dan elongasi sebesar 18,95%. Plastik biodegradable juga mampu terurai dalam waktu dua minggu.Kata kunci: gliserol, plastik biodegradable, tandan kosong kelapa sawit